MYOCARDIAL INFARCTION IN YOUNG VERSUS OLDER ADULTS: CLINICAL CHARACTERISTICS AND ANGIOGRAPHIC FEATURES - Shah, S. Sadiq; Noor, Lubna; Shah, Syed Habib; sawar, Shah; Din, Shahab Ud; Awan, Zahid Aslam; Hafizullah, Muhammad (Journal of Ayub Medical College Abbottabad, 2010)
Background: Coronary artery disease is now frequently encountered in young adult population. However, being a relatively uncommon entity, not many studies are available in this regard. Therefore, the present study was designed to evaluate the clinical characteristics and angiographic features of patients less than 40 years of age with a history of myocardial infarction and compare them to patients older than 40 years. Methods: A total of 281 patients who underwent coronary angiography from April, 2009 to December, 2009, were included in this study. The patients were divided into two groups on the basis of age. Group A included patients 40 years of age or younger. Group B included patients older than 40 years. Both the groups were compared with respect to gender, hypertension, diabetes mellitus and extent and severity of coronary artery disease as assessed on coronary angiography. Results: Of the total 281 patients, 45 (16%) were ‰¤40 years old (Group-A) and 236 (84%) were older than 40 years (Group-B). There was no significant difference between the two groups with respect to the risk factors like gender, hypertension and diabetes mellitus. On coronary angiography, the two groups neither differed in the number of totally occluded vessels, nor in the severity of the culprit lesion. There were only 3 patients in group-A (6.7%) and 5 patients in group-B (2.1%) with normal coronaries (p=NS). Majority (60%) of the patients in group-A had no significant disease or single vessel disease while majority (69%) of the patients in group-B had two or more vessels involved (p<0.001). As far as the number of lesions in the coronary arteries is concerned, 62.3% patients had 2 or lesser lesions in group-A while 68.6% patients in group-B had three or more lesions (p=0.001). Conclusion: These data suggest that in our study, young patients with MI do not have significantly high prevalence of normal coronaries compared to older patients. Young patients are similar to the older patients with respect to severity of CAD. Lesser number of coronaries is involved and there is lesser number of lesions per patient in young patients compared to older ones. Keywords: Coronary Artery Disease (CAD), Myocardial infarction (MI), Coronary Angiography, Risk Factors